Updates on Brucellosis 2015
DOI: 10.5772/61325
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Brucella spp. in Domestic and Wild Animals

Abstract: Brucella spp. is the aetiological agent of brucellosis, a serious contagious disease that results in reproductive failure and that has profound public health significance because of its zoonotic characteristics. This disease also is responsible for a high economic impact associated with the application of prevention, surveillance and test-andslaughter programmes in animals by national authorities. Brucella spp. infects a large variety of animals and their prevalence is variable worldwide, mainly associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 122 publications
1
16
1
1
Order By: Relevance
“…Sex dependent prevalence has been documented in cattle and small ruminants, i.e., B. melitensis is more often found in females. Hence, this phenomenon in pigs has not fully been investigated, it may affect both sexes (male and female) equally [37]. In this study, higher prevalence was found in male pigs than in female pigs.…”
Section: Discussionmentioning
confidence: 60%
“…Sex dependent prevalence has been documented in cattle and small ruminants, i.e., B. melitensis is more often found in females. Hence, this phenomenon in pigs has not fully been investigated, it may affect both sexes (male and female) equally [37]. In this study, higher prevalence was found in male pigs than in female pigs.…”
Section: Discussionmentioning
confidence: 60%
“…Identification of risk factors is crucial for control of brucellosis. Animal related risk factors (age, sex, breed and species), farm management, geographical distribution, herd management and farmers‘ awareness of brucellosis have been associated with the prevalence of brucellosis [ 46 ]. In this study, the seroprevalences of age groups were 22.9% (52/227), 27.9% (19/68), 13.7% (7/51) and 25.7% (9/35) in animals of <8 years, ≥8–11 years, 11–13 years and >13–15 years using i-ELISA, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Brucellosis has been reported from different species of animals worldwide including marine mammals [31]. It is one of the most economically important diseases of animals worldwide [32], yet, information related to the prevalence of brucellosis is still sparse from the developing world and there is need to address this paucity of literature from the developing world because eradication of brucellosis would not be lasting if many other parts of the world are still struggling with endemic brucellosis [33].…”
Section: Animal Brucellosismentioning
confidence: 99%